Analysis of Question in Class IX MTs Akidah Aklhlak Books - Fatimatuzzahro (Department of Teacher Professional Education, Tarbiya and Teacher Training Faculty, UIN Sunan Gunung Djati Bandung, 2023)
Analysis of the items in the Aqidah Akhlak Class IX book is an effort to improve the quality of education through evaluation,given the urgency of evaluating learning as a benchmark for student success, it is necessary to have an analysis that can later improve the quality. In learning evaluation, we are familiar with the terms HOTS, MOTS, and LOTS questions. In a question formulation, of course there must be accuracy in making it, both context, level of difficulty, KKO, and others. The purpose of the analysis of the items in the class IX Mts Aqidah Akhlak subject can later become an analysis that can improve the quality of the next questions. The inadequacy of the questions in the subject book will make the level of a child's thinking ability less developed.